Pengaruh Head terhadap Kinerja Mekanis Sebuah Kompresor sebagai Turbin (Compressor as Turbine/CAT) - Muhammad Fikri Zahran; Yul Hizhar; Uyung Gatot Syafrawi Dinata (Universitas Muhammadiyah Metro, 2026)
This study aims to evaluate the mechanical performance of a turbocharger compressor operated as a water turbine. The article presents experimental results on the effect of head variation on the performance of a Compressor as Turbine (CAT). The experiments were conducted using a laboratory test rig under three head levels: 8, 10, and 12 meters. The main parameters analyzed include rotational speed, torque, turbine output power, and efficiency, all measured systematically. The experimental results indicate that the CAT system achieved stable operation and the highest energy conversion efficiency within the rotational speed range of 1000 to 2000 rpm. Within this range, flow rate, torque, and output power demonstrated a consistent relationship that produced a maximum efficiency of approximately 70%. The variation in head had a significant effect on performance, with applications at 10–12 meters head yielding more optimal results. These findings suggest that the turbocharger compressor has promising potential as an efficient and cost-effective water turbine solution, offering a balance between performance and economic feasibility. Moreover, this study contributes new experimental data to the development of CAT technology, which may accelerate its implementation in sustainable energy systems.